Perceptions of Physical Activity and the Use of Activity Monitors to Increase Activity Levels in Patients Undergoing Total Knee Replacement - Kaetlyn R. Arant (Wiley, 2021)
Objective Although most total knee replacement (TKR) recipients report less pain and improved function after TKR, many remain sedentary. We aimed to understand TKR recipients’ motivations for undergoing TKR, perceptions of and goals related to physical activity, and the role, if any, that activity monitors might play in their recovery. Methods We conducted a qualitative study, individually interviewing 27 participants who had recently undergone or were about to undergo TKR. We conducted a thematic analysis to better understand participants’ views of the benefits and barriers to physical activity after TKR. Results We identified nine themes and one subtheme that identify patients’ initial motivations for undergoing TKR and may help TKR recipients achieve increased activity levels and a perceived successful recovery. Some key messages that emerged from our work include the following: exercise is necessary for physical and mental health, pain and functional limitation interfere with daily life, tracking steps motivates individuals to increase activity levels, and different incentives (for engaging in physical exercise and using an activity monitor) are effective for different individuals. Conclusion Participants recognized the health benefits of physical activity, and many believed activity monitor use would help them become more active after surgery. Both external and internal factors played a role in motivating individuals to become more active and wear activity monitors.